An investigation into the relationship between equine behaviour when tacked‐up and mounted and epaxial muscle hypertonicity or pain, girth region hypersensitivity, saddle‐fit, rider position and balance, and lameness. (2nd February 2021) - Dyson, S.; Bondi, A.; Routh, J.; Pollard, D.
Summary: Background: Reasons for abnormal behaviour during tacking‐up and mounting are poorly documented. Objectives: To relate behavioural abnormalities during tacking‐up or mounting to epaxial muscle hypertonicity or pain, girth region hypersensitivity, ill‐fitting tack, rider position and balance, or equine musculoskeletal pain. Study design: Prospective observational study; convenience sample of 193 horses. Methods: The behaviour of horses in a stable or tied up was observed for ≥8 min before systematic palpation of the thoracolumbosacral and girth regions. Owners were asked to tack‐up and mount using their normal regime. A purpose‐designed protocol for assessment of behaviour during tacking‐up and mounting was applied. Lameness was evaluated in‐hand and during ridden exercise. Static and dynamic saddle‐fit were assessed. A static saddle‐fit score was the sum of any saddle‐fit abnormality. Rider position in the saddle, balance and size relative to the saddle were evaluated during ridden exercise. Multivariable negative binomial regression modelling was used to assess the relationship between the sum of tacking‐up and mounting behaviours and horse, rider and tack‐fit variables. Results: Riding School horses comprised only 12% of the sample population, but had higher rates of abnormal behaviours during both tacking‐up (P<0.0001) and mounting (P = 0.007) compared with General Purpose horses. The rate of abnormal behaviour during tacking‐up for horses with moderate or severe lameness was 1.4 times higher (P = 0.02) than for nonlame horses. Horses with lameness in‐hand or ridden had 1.5 times higher rates of abnormal behaviour during mounting than nonlame horses. Tight tree points (P = 0.03) and epaxial muscle pain (P<0.001) were associated with higher behaviour scores during tacking‐up. Higher static saddle‐fit scores were associated with higher behaviour scores during mounting. Main limitations: Oral examination was not performed. Conclusions: The display of many behaviours during tacking‐up or mounting is likely to reflect lameness or tack‐associated discomfort. Owners must be better educated to recognise these behaviours.